Hubungan Daya Terima Makanan dengan Tingkat Kecukupan Energi dan Protein Taruna di Asrama Politeknik Ilmu Pelayaran Semarang - Hidayatus Sholehah; Agus Sartono; Mufnaetty - (Jurnal Gizi, 2015)
Food service is the provision of food in large quantities starts from menu planning to food distribution.The aims of Food Service is to reached the satisfaction level of the consumers nutritional status. Polytechnic Institute of Science Shipping Semarang is a government agency that is carrying out the food service for cadets who live in the dorm. The goal is to ensure the health status of cadets in order to follow all the learning activities and other activities that is high in terms of physical activity.The purpose of the study was to determine the level of acceptance of the food menu that’s provided by Dormitories Sailing Science Polytechnic Semarang and its relation to cadet’s energy and protein adequacy level. This type of research is analytic research in the field of nutrition with a cross-sectional approached. The sample used in the study were 36 people taken by sistematic random sampling.The results of the study showed that all of the cadets can receive boarding with good food, with an average acceptance rate of 99.85 % ±0,263 % of the food served. The average of energy intake of cadets from the dorm food is 1657.25 ± 163.883 kcal per day. The average of protein intake is 50.33 g ±3.038 g per day. The average of dorm food donations towards cadet’s energy sufficiency level is 58.74 % ± 7.963 % of energy adequacy rate recommended. The average of protein is 77.46 % ±9.407 % of protein adequacy rate recommended. Pearson correlation test results showed there is no relationship between the level of acceptance the dormitories food with the sufficiency level of energy and protein.Polytechnic Institute of Science Semarang need to realize the standard of menu. Cruise portion that has been made more consistent to improve the contribution of energy and protein intake of food dormitory, and add a menu cycle so that variations in the dorm food is more diverse.